Existence results for boundary-value problems with nonlinear fractional differential inclusions and integral conditions. - Hamani, Samira; Benchohra, Mouffak; John R, Graef (Electronic Journal of Differential Equations (EJDE)[electronic only], 2010)
In this article, the authors establish sufficient conditions for the existence of solutions for a class of boundary value problem for fractional differential inclusions involving the Caputo fractional derivative and nonlinear integral conditions. Both cases of convex and nonconvex valued right hand sides are considered. The topological structure of the set of solutions also examined.